Rentabilidad de los contratos de obra pública (2020)
Colombian law has established some requirements that must be fulfilled by the entity during the planning stage to determine the object ́s value to be hired, among which is know the relative object ́s sector of the hiring process from the financial perspective. In this determined value by the entity are established the income and costs in which the contractor will incur to develop the project, and its difference is considered the estimated gross utility that must be according to the sector where is developed.